Effect of Pretreatment Methods on the Formation of Advanced Glycation End Products in Fried Shrimp - Runlin Wu; Caihua Jia; Jianhua Rong; Shanbai Xiong; Ru Liu (Foods, 2023)
Fried shrimp are popular for their attractive organoleptic and nutritional qualities. However, consumers are more concerned about the safety of fried foods. To investigate the formation of advanced glycation end products (AGEs) in fried shrimp and provide pretreatment guidance for producing low-AGEs fried pacific white shrimp were treated with seven pretreatment methods before frying. The AGEs contents, physicochemical indicators, and their correlations in the fried shrimps’ interior, surface, and batter layer were analyzed. Results indicated that pretreatment methods influenced both Maillard and oxidation reactions by altering the basic compositions, which controlled the formation of AGEs. The highest and lowest AGEs contents were obtained in shelled shrimp with exscinded back and whole shrimp, respectively. The batter-coated treatment reduced the AGEs contents in samples but increased the oil content. Correlation analysis showed that lipid oxidation was the decisive chemical reaction to the formation of AGEs by promoting the generation of dicarbonyl compounds and their combination with free amino acids. Conclusively, the whole shrimp was suitable for producing fried shrimp with low AGEs, oil content, and desirable color.